The Development of the Regional Oak Tree-ring Chronology from the Roman Sites in Celje (Slovenia) and Sisak (Croatia) - Durman, Aleksandar (2009)
Based on a high similarity between the Celje and Sisak chronologies authors tried to join both chronologies into a single regional chronology. Material from Sisak significantly crossdated with material from Slovenia. That gives an enormous potential to crossdate oak material from different parts of the Balkan Peninsula and also encourages further research in this region.
Projekt MZOS
ENG